A comprehensive review and clinical guide to molecular and serological diagnostic tests and future development: In vitro diagnostic testing for COVID-19 - Yonrapach Areerob; Suresh Sagadevan; Won-Chun Oh (My University, 2023)
Abstract COVID-19 is a contagious syndrome caused by SARS Coronavirus 2 (SARS-CoV-2) that requires rapid diagnostic testing to identify and manage in the affected persons, characterize epidemiology, and promptly make public health decisions and manage the virus present in the affected person and promptly make public health decisions by characterizing the epidemiology. Technical problems, especially contamination occurring during manual real-time polymerase chain reaction (RT-PCR), can result in false-positive NAAT results. In some cases, RNA detection technology and antigen testing are alternatives to RT-PCR. Sequencing is vital for tracking the SARS-CoV-2 genome’s evolution, while antibody testing is beneficial for epidemiology. SARS-CoV-2 testing can be made safer, faster, and easier without losing accuracy. Continued technological advancements, including smartphone integration, will help in the current epidemic and prepare for the next. Nanotechnology-enabled progress in the health sector has aided disease and pandemic management at an early stage. These nanotechnology-based analytical tools can be used to quickly diagnose COVID-19. The SPOT system is used to diagnose the coronavirus quickly, sensibly, accurately, and with portability. The SPOT assay consists of RT-LAMP, followed by pfAgo-based target sequence detection. In addition, SPOT system was used to detect both positive and negative SARS-CoV-2 samples. This combination of speed, precision, sensitivity, and mobility will allow for cost-effective and high-volume COVID-19 testing.
Keywords: Software portability; Pandemic; Gold standard (test); SARS-CoV-2 detection and testing